2019
DOI: 10.3390/ijms20030544
|View full text |Cite
|
Sign up to set email alerts
|

Developing LRP1 Agonists into a Therapeutic Strategy in Acute Myocardial Infarction

Abstract: Cardioprotection refers to a strategy aimed at enhancing survival pathways in the injured yet salvageable myocardium following ischemia-reperfusion. Low-density lipoprotein receptor-related protein 1 (LRP1) is a multifunctional receptor that can be targeted following reperfusion, to induce a cardioprotective signaling through the activation of the reperfusion injury salvage kinase (RISK) pathway. The data from preclinical studies with non-selective and selective LRP1 agonists are promising, showing a large the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 110 publications
2
28
0
Order By: Relevance
“…One of the fragments of the cleaved RCL is inserted into the central beta-sheet of A1AT in both pathways, whereas the other fragment (36-aa) is released into the solvent. Notably, the 36-aa fragment is produced as a result of proteolytic cleavage by several serine proteases and possesses physiologic functions ( Blaurock et al, 2016 ; Potere et al, 2019 ; Risor et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the fragments of the cleaved RCL is inserted into the central beta-sheet of A1AT in both pathways, whereas the other fragment (36-aa) is released into the solvent. Notably, the 36-aa fragment is produced as a result of proteolytic cleavage by several serine proteases and possesses physiologic functions ( Blaurock et al, 2016 ; Potere et al, 2019 ; Risor et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endocytic function and signaling properties confer a major role to LRP1 in the pathophysiology of numerous diseases such as hepatic steatosis, kidney fibrosis, acute respiratory distress syndrome (ARDS), Alzheimer's disease (AD) and atherosclerosis (23). In addition, recent evidences showed that LRP1 is implicated in the pathophysiological mechanisms underlying AMI, IRI and adverse LV remodeling (20, 21).…”
Section: Low-density Lipoprotein Receptor-related Protein 1 (Lrp1): Gmentioning
confidence: 99%
“…LRP1 initiates signaling by direct ligand binding or, through its co-receptors, transactivates signal pathways. Although the exact mechanisms have been partly elucidated, the tyrosine phosphorylation at the NPxY motifs is necessary for LRP1-mediated signal transduction (21, 23, 27).…”
Section: Low-density Lipoprotein Receptor-related Protein 1 (Lrp1): Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the potentiation of cardiomyocyte survival should be considered as a valuable alternative to be coopted in the treatment of MIRS. An interesting approach is the modulation of the low-density lipoprotein receptor-related protein 1 (LRP1), which is able to both downregulate the NF-κB-related inflammation during MIRS and enhance cardiomyocyte survival through the activation of the PI3K/Akt and ERK1/2 pathways in such cells, as thoroughly reviewed in [115]. As an example of this approach, a clinical trial using plasma-derived alpha-1 antitrypsin, an agonist of the LRP1 receptor, showed shorter time-to-peak creatine kinase myocardial band (CK-MB) values [116] in relation to a significant reduction on CRP [117] (Table 1).…”
Section: Immunoregulation As a Modern Alternative To Immunosuppressionmentioning
confidence: 99%